2015
DOI: 10.1109/tmi.2015.2427739
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Prostate Cancer Detection Using Ultrasound RF Time Series: In Vivo Feasibility Study

Abstract: Ultrasound RF time series results in differentiation of cancerous and normal tissue with high AUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
0
29
1
Order By: Relevance
“…The histopathology information was then overlaid on the ex vivo MR images and subsequently registered to the in vivo ultrasound images. The registration process performed on this data was previously published by Imani et al [21]. …”
Section: Temporal Enhanced Ultrasound Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The histopathology information was then overlaid on the ex vivo MR images and subsequently registered to the in vivo ultrasound images. The registration process performed on this data was previously published by Imani et al [21]. …”
Section: Temporal Enhanced Ultrasound Datamentioning
confidence: 99%
“…TeUS Data from the 9 subjects, whose benign and malignant ROIs are clearly labeled, is used in the analysis described here. The ROIs were selected in a way that maximizes the distance between benign and malignant ROIs to avoid mislabeling (see [21] for details regarding the ROI selection process). The number of ROIs per patient, along with GSs of primary and secondary lesions per slice are shown in Table I.…”
Section: Temporal Enhanced Ultrasound Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1 Different feature sets extracted from these signals have been successfully applied to various classification problems for distinguishing cancerous and benign tissue in both ex vivo 1, 2 and in vivo [3][4][5][6] studies. These studies have demonstrated that the tissue classification results with temporal ultrasound outperforms conventional tissue typing approaches, including B-mode texture analysis and spectral methods.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 TeUS is produced by sonicating tissue over a short period of time, without intentionally moving the tissue or the transducer. The result is a sequence (time series) of Radio Frequency (RF) ultrasound frames.…”
mentioning
confidence: 99%